Nonmalignant portal vein thrombi in patients with cirrhosis consist of intimal fibrosis with or without a fibrin‐rich thrombus. Issue 4 (5th December 2021) - Driever, Ellen G.; von Meijenfeldt, Fien A.; Adelmeijer, Jelle; de Haas, Robbert J.; van den Heuvel, Marius C.; Nagasami, Chandrasekaran; Weisel, John W.; Fondevila, Constantino; Porte, Robert J.; Blasi, Anabel; Heaton, Nigel; Gregory, Stephen; et al.
Abstract: Background and Aim: Portal vein thrombosis (PVT) is a common complication of cirrhosis. The exact pathophysiology remains largely unknown, and treatment with anticoagulants does not lead to recanalization of the portal vein in all patients. A better insight into the structure and composition of portal vein thrombi may assist in developing strategies for the prevention and treatment of PVT. Approach and Results: Sixteen prospectively and 63 retrospectively collected nonmalignant portal vein thrombi from patients with cirrhosis who underwent liver transplantation were included. Histology, immunohistochemistry, and scanning electron microscopy were used to assess structure and composition of the thrombi. Most recent CT scans were reanalyzed for thrombus characteristics. Clinical characteristics were related to histological and radiological findings. All samples showed a thickened, fibrotic tunica intima. Fibrin‐rich thrombi were present on top of the fibrotic intima in 9/16 prospective cases and in 21/63 retrospective cases. A minority of the fibrotic areas stained focally positive for fibrin/fibrinogen (16% of cases), von Willebrand factor (VWF; 10%), and CD61 (platelets, 21%), while most of the fibrin‐rich areas stained positive for those markers (fibrin/fibrinogen, 100%; VWF, 77%; CD61, 100%). No associations were found between clinical characteristics including estimated thrombus age and use of anticoagulants and presence of fibrin‐rich thrombi. Conclusion: We demonstrate that PVT in patients with cirrhosis consists of intimal fibrosis with an additional fibrin‐rich thrombus in only one‐third of cases. We hypothesize that our observations may explain why not all portal vein thrombi in patients with cirrhosis recanalize by anticoagulant therapy.